Establishment of a Jaw Fibrosarcoma Patient-Derived Xenograft and Evaluation of the Tumor Suppression Efficacy of Plumbagin Against Jaw Fibrosarcoma - Xin, Yuqi; Li, Shiya; Jiang, Qingkun; Hu, Fangling; He, Yuanqiao; Zhang, Jie (Frontiers in Oncology, 2020)
Background: Head and neck fibrosarcoma is a rare malignant tumor, accounting for about 1% of all head and neck tumors. It can also occur in the jaw bone, for which surgical resection is the main treatment but the recurrence rate is high and the prognosis is usually poor. Due to the lack of models mimicking the biological characteristics of the tumor, there is little progress in the research of the pathogenesis and treatment of fibrosarcoma. Therefore, there is an urgent need to explore a highfidelity model that can reflect the biological characteristics of fibrosarcoma for the sake of improving the therapeutic outcome and prognosis, and preventing recurrence. Patient-derived xenografts (PDX) may more accurately reflect the human disease, and is an attractive platform to study disease biology and develop treatments and biomarkers. In this study we describe the establishment of jaw fibrosarcoma PDX models and compare PDX tumors to the human original.